2016
DOI: 10.1016/j.jalz.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tau positron emission tomography tracer [18F]AV‐1451 binding to postmortem tissue in Alzheimer's disease, primary tauopathies, and other dementias

Abstract: [F]AV-1451 binds to tau in AD, and some other tauopathies. However, evidence for a non-tau binding site and lack of correlation between tracer binding and antibody staining suggest that reliable quantification of tau load with this tracer is problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
202
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(221 citation statements)
references
References 29 publications
12
202
2
1
Order By: Relevance
“…It is therefore plausible that the high expression of 4R tau in the Tau(4RD*LM)-YFP(2) cells is seeded by the 4R component of tau prions in AD and CTE. It is noteworthy that the [ 18 F]AV-1451 PET tracer selectively binds to pathologic tau in AD patient samples compared with PSP and PiD patient samples (57)(58)(59), suggesting a conformation difference may exist between tau in AD versus tau in the isoform-specific tauopathies. Our conclusion, that AD prions contain both 3R and 4R tau isoforms, whereas PSP and PiD contain either 4R or 3R, respectively, provides one possible explanation for the results reported for [ 18 F]AV-1451.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore plausible that the high expression of 4R tau in the Tau(4RD*LM)-YFP(2) cells is seeded by the 4R component of tau prions in AD and CTE. It is noteworthy that the [ 18 F]AV-1451 PET tracer selectively binds to pathologic tau in AD patient samples compared with PSP and PiD patient samples (57)(58)(59), suggesting a conformation difference may exist between tau in AD versus tau in the isoform-specific tauopathies. Our conclusion, that AD prions contain both 3R and 4R tau isoforms, whereas PSP and PiD contain either 4R or 3R, respectively, provides one possible explanation for the results reported for [ 18 F]AV-1451.…”
Section: Discussionmentioning
confidence: 99%
“…These tracers showed in vitro high specificity to tau pathology (specifically to 3r/4r paired helical filamentous tau aggregates that are characteristic of AD), although the agreement between tracer binding and tau immunohistochemistry appears more complex. [67][68][69][70][71] The favourable pharmacokinetics of those tracers [72][73][74] completed the requirements for Phase I. A number of rather small and non-consecutive Phase II studies have already reported good discrimination between healthy volunteers and AD patients, 67,[75][76][77][78] with preliminary evidence, available for only one of the tracers (AV-1451), supporting the agreement between antemortem PET quantification of the tracer retention and postmortem evidence of tau pathology in the same non-AD patients, a carrier of a MAPT mutation (p.R406W), and two patients with corticobasal degeneration, although questions remain about the specific target of the tracer 58,79,80 (Phase II, SA 2).…”
Section: Sa3mentioning
confidence: 99%
“…Autoradiography studies using human brain tissue samples from multiple neurodegenerative disorders have largely confirmed the specific binding of FTP to paired helical filaments (PHF) tau-containing neurofibrillary tangles and dystrophic neurites in AD brains. In comparison, FTP binding is absent or very low in tau aggregates comprised by straight filaments as well as in alpha-synuclein or TDP-43 deposits [69]. …”
Section: Introductionmentioning
confidence: 99%